2005
DOI: 10.1111/j.1570-7458.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of the reproductive system of female Leptinotarsa undecimlineata

Abstract: The effect of a non-host plant, Solanum myriacanthum , on ovarian dynamics and longevity of Leptinotarsa undecimlineata (Stål) (Coleoptera: Chrysomelidae) was studied under laboratory conditions. Females reared on the natural host, S. lanceolatum , served as controls . Female beetles did not accumulate eggs on the non-host. After continuous exposure to S. myriacanthum , the production of basal oocytes was diminished and oocytes were reabsorbed. Oocyte size, however, was not affected when compared to females fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It seems that the effect of larval experience on adult preferences (i.e., preimaginal conditioning) is limited in holometabolous insects (Harrison, 1987; Lu & Logan, 1994; Rojas & Watt, 1999; Barron, 2001; Hora et al., 2005). Adult fecundity, however, is to a large extent affected by host plant quality (Awmack & Leather, 2002), and the data presented here showed that S. myriacanthum is a poor host for female feeding and reproductive development (López‐Carretero et al., 2005). Females fed with S. myriacanthum ate leaves during fewer days than control females in the 40‐day feeding experiments, and remained motionless until the end of the experiment (A Eben & A López‐Carretero, unpubl.).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It seems that the effect of larval experience on adult preferences (i.e., preimaginal conditioning) is limited in holometabolous insects (Harrison, 1987; Lu & Logan, 1994; Rojas & Watt, 1999; Barron, 2001; Hora et al., 2005). Adult fecundity, however, is to a large extent affected by host plant quality (Awmack & Leather, 2002), and the data presented here showed that S. myriacanthum is a poor host for female feeding and reproductive development (López‐Carretero et al., 2005). Females fed with S. myriacanthum ate leaves during fewer days than control females in the 40‐day feeding experiments, and remained motionless until the end of the experiment (A Eben & A López‐Carretero, unpubl.).…”
Section: Discussionmentioning
confidence: 82%
“…Solanum chrysotrichum , S. diversifolium , S. lanceolatum , S. ochraceoferrigineum , S. saponeceum , and S. torvum have been described as host plants for L. undecimlineata in Mesoamerica (Hsiao, 1986, 1988; Cañas et al., 2002; O’Neil et al., 2005). Solanum lanceolatum and S. ochraceoferrigineum are common hosts in Mexico (Jacques, 1988; López‐Carretero et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an agroeconomic point of view, decreased reproduction (lower number of laid eggs and lower fertility and fecundity) is one the most important insecticidal effects, and malfunctions and malformations of the reproductive system can be induced by glycoalkaloids. The disruptive toxic effects of Solanaceae plants on insect reproductive systems have been shown; insects reared on non-host plant species revealed diminished production of oocytes and increased reabsorption of formed oocytes, which inhibits the maturation of eggs [ 61 ]. These authors postulate that the glycoalkaloids present in the leafs of non-host plant species may interact with the endocrine system of pests, especially altering juvenile hormone-like activity, similarly to other glycoalkaloids [ 62 ], thus disturbing insect development.…”
Section: Solanaceae Secondary Metabolitesmentioning
confidence: 99%
“…This process is proposed to be an adaptive mechanism to optimize fitness in hostile environments such as parasitic attack or lack of mates, food or host substrate (Bell & Bohm, 1975; Ohgushi, 1996; Rosenheim et al. , 2000; Kotaki, 2003; Wang & Horng, 2004; Lopez‐Carretero et al. , 2005; Barrett et al.…”
Section: Introductionmentioning
confidence: 99%